Analisis Nilai Tambah dan Pemasaran Produk Bandeng Isi pada Home Industry Bunda Juminah Food (Bjf), Bandung - -, Junianto; Fatharani, Nadira; Putri, Dinda Tazkia; Fitriandes, Muhammad Thariq Aziz; Sj, Fanny Azis Roihan (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2024)
This research aims to analyze the added value and marketing of home industry stuffed milkfish products "Bunda Juminah Food (BJF)". Bunda Juminah Food UMKM is located in the Bumi Panyileukan Complex, Jalan Sauyunan V Blok F5 No.5, Cipadung Kidul Village, Panyileukan District, Bandung City. The research method used is the survey method. Survey activities were carried out in March 2024. Data was obtained by conducting direct interviews in the field with the home industry owner Bunda Juminah Food (BJF). The data obtained was analyzed and the amount of added value was calculated using the Hayami method. The analysis related to marketing is carried out descriptively. . Based on the research results, it can be seen that the calculation of the added value of production results in one production process is 17 kg with the use of 20 kg of raw materials. The product/output value in the calculation is IDR 38,250 with an added value of IDR 5,250. Consumers selling Bunda Juminah Food (BJF) products are part of the adventure food consumer segment who most like marketing in the form of events, promoting their products using social media and utilizing the facilities and amenities provided by the West Java Province Maritime and Fisheries Service through bazaars. Product production is based on consumer demand, as well as marketing distribution, ordering products is carried out online, then the product distribution process relies on delivery by online motorcycle taxis to consumers' locations.